Determinants of hotel occupancy rate in a Chinese gaming destination. (March 2015) - Lei, Weng Si (Clara); Lam, Ching Chi (Cindia)
Abstract: This paper aims to investigate factors affecting the hotel occupancy rate of the sole official gaming destination in China – Macao. Data from 39 hotels (3–5 stars) during the period of 2008–2011 have been applied. Three categories of determinants forming nine hypotheses were tested and all are supported except seasonality. Eight factors were identified exercising significant influences on the hotel occupancy rate in the destination. A regression model of 51.5% predictability is generated to predict the hotel occupancy rate in the destination. The study is concluded with insights to hoteliers who are interested to invest or operate in a gaming destination.